Pengaruh Kompetensi Kepribadian Guru Pendidikan Agama Kristen Dan Budi Pekerti Terhadap Perkembangan Moral Siswa Kelas V di SD Negeri No 030286 Parsaoran Kabupaten Dairi Tahun Pembelajaran 2023/2024 - Junita Sinaga; Tiurma Berasa; Tianggur Medi Napitupulu; Lustani Samosir; Hasudungan Simatupang (Sekolah Tinggi Pastoral Kateketik Santo Fransiskus Assisi, 2024)
This research aims to determine the influence of personality competence of Christian Religious Education and Character Education teachers on the moral development of class V students at State Elementary School No. 030286 Parsaoran, Dairi Regency, Academic Year 2023/2024. Hypothetically, there is a positive influence between the personality competence of Christian Religious Education teachers and Characteristics on the moral development of class V students at State Elementary School No. 030286 Parsaoran for the 2023/2024 Academic Year. The research method uses a quantitative and descriptive approach. The population of all class V students at State Elementary School No. 030286 Parsaoran for the 2023/2024 academic year who are Protestant Christians is 36 people. This research is population research. The research instrument is a closed questionnaire. The results of data analysis obtained: a) The value of rcount=0.559>rtable=0.329 shows that there is a positive relationship between the personality competence of Christian Religious Education and Character Education teachers and the moral development of class V students at State Elementary School No. 030286 Parsaoran for the 2023/2024 Academic Year. b) The regression equation has an influence of 31.25%. Yˆ = 50,13 + 0,51X . c) The determination test determines the magnitude of the research. It concludes that there is a positive influence of the personality competence of Christian Religious Education and Character Education teachers on the moral development of class V students at State Elementary School No. 030286 Parsaoran for the 2023/2024 Academic Year.